The Brain Frame – From Molecules To Behaviour - Mehnaz Nuruddin Gitay (Journal of the Dow University of Health Sciences, 2015)
Since the beginning of time, behaviour of acquaintances, friends and family has been a matter of intense interest. Behavioural issues have, since then, imposed threats to human race as either evil spirits or insidious offences. To address these concerns, social, theological and scientific communities have played a vivid role, bringing to light the underlying secrets of their respective domains. Present literature shall highlight the revelations made by the scientific community regarding behaviour. According to science, behaviour is the outcome of multiple processes taking place within the body as influenced by the external environment. The external environment includes the behaviour of fellow beings, the weather and the environment (political, economic, social and technological). The food we eat shapes the internal chemical environment by providing materials to the available genetic and molecular base of the body. The molecules of the body include hormones, enzymes as well as energy providing substances like carbohydrates and fats, and structure making molecules, proteins. Any change in the external or internal body environment that imposes a demand to adapt is known as stress. Acute stress is controlled and the body adapts under the influence of physiological changes including the cortisol related cascade on top of the list. Chronic stress is beyond the physiological control leading to exhaustion of the adaptation process. This may lead to depression finally.